1992
DOI: 10.1002/bjs.1800790933
|View full text |Cite
|
Sign up to set email alerts
|

Biodistribution of Lipiodol following hepatic arterial injection

Abstract: Thirteen patients undergoing selective coeliac angiography before insertion of an indwelling hepatic arterial cannula underwent injection of 3 ml radiolabelled Lipiodol (2 MBq 131I) into the hepatic artery at the end of the procedure. At subsequent laparotomy 1-9 days later, biopsies were taken from normal liver and metastases. The radioactivity of this material was measured to establish the tumour:liver ratios. Two patients with large metastases (> 10 cm in diameter) had low ratios. In the remainder, the medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

1994
1994
2012
2012

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…Ethiodol is thought to have no antitumor activity itself, and although it is not truly an embolic agent, it is possible that it may cause temporary microembolic phenomenon that could potentiate drug efficacy (10). It is more plausible, however, that Ethiodol is simply a vehicle for drug delivery, with unique sustained release characteristics that may be related to its density, and the selective retention in tumors probably occurring because of poor tumor venous and lymphatic drainage (11)(12)(13)(14).…”
Section: Discussionmentioning
confidence: 97%
“…Ethiodol is thought to have no antitumor activity itself, and although it is not truly an embolic agent, it is possible that it may cause temporary microembolic phenomenon that could potentiate drug efficacy (10). It is more plausible, however, that Ethiodol is simply a vehicle for drug delivery, with unique sustained release characteristics that may be related to its density, and the selective retention in tumors probably occurring because of poor tumor venous and lymphatic drainage (11)(12)(13)(14).…”
Section: Discussionmentioning
confidence: 97%
“…For metastases of colorectal cancer (CRC), mean ratios of tumor/liver uptake were 1.5-3 after 1 day and 2.6 at 3-9 days, however after exclusion of large lesions with low uptakes [23,24]. Tumor doses were 12-43 Gy/GBq, 1.2-4.7 times higher than those to the liver [24].…”
Section: Lipiocismentioning
confidence: 96%
“…Lipiodol labeled with iodine 131 ( 131 I-lipiodol) injected into the hepatic artery has been investigated for clinical applications after its biodistribution had been tested for safety and utility. 4 It has been considered to be an effective treatment for patients with unresectable HCC. 5 Our hypothesis was that it may also eradicate the residual microscopic disease or kill cells with high-grade dysplasia in the liver remnant after liver resection.…”
Section: Arch Surg 2000;135:1298-1300mentioning
confidence: 99%
“…It has been demonstrated that, following hepatic arterial injection of radiolabeled lipiodol, activity remains high within the tumors while being cleared from the normal liver to be excreted in the urine. 4 There is little doubt that injection of lipiodol into the hepatic artery is not only effective for aiding in the diagnosis of HCC by postlipiodol CT but also has by itself some kind of therapeutic efficacy. Moreover, results of transcatheter oily chemoembolization were comparable at 5 years with those of resection and transplantation in a retrospective series.…”
Section: Follow-upmentioning
confidence: 99%